Analysis of structural and vascular changes of the optic disc and macula in different stages of primary open angle glaucoma - Petrović, Maja; Resan, Mirko; Stanković Babić, Gordana; Šarenac Vulović, Tatjana; Radenković, Marija; Veselinović, Aleksandar; Trenkić, Marija; Cvetanović, Marija (Vojnosanitetski pregled, 2022)
Background/Aim. It is possible that patients with open-angle glaucoma be asymptomatic in the early stage of the disease. The aim of this study was to determine the structural and vascular changes of the optic disc (OD) and macula in healthy and primary open-angle glaucoma (POAG) eyes, detected by optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) as well as the correlation of the OCT and OCTA measurements and their association with the presence of POAG. Methods. A total of 196 eyes were included and classified into four groups, out of them 48 were healthy eyes, 51 eyes were with mild POAG, 50 eyes with moderate POAG, and 47 eyes with advanced glaucoma. All subjects underwent standard ophthalmic examination. OCT measured the mean, superior and inferior retinal nerve fiber layer (RNFL) thickness and macular ganglion cell complex (GCC). OCTA evaluated the vessel capillary density (VCD) in OD, foveal avascular zone (FAZ) and macular vessel density (VD) in the superficial (SL) and deep (DL) retinal vascular plexus. Results. Patient characteristics were similar except for decreased visual acuity, thinner corneas, higher intraocular pressure and higher cup/disc ratio in POAG patients. OCT results showed that RNFL and GCC thickness gradually decreased according to POAG severity. Within the assessment conducted by OCTA, VCD’s value in OD also diminished with the progression of POAG, having the lowest value in patients with advanced glaucoma. The same pattern was observed in vessel density around FAZ and VD values. Comparing the structural and vascular changes, a significant positive correlation was found between RNFL thickness and VCD inside OD, and GCC and VD SL in the macular zone. Conclusion. OCT and OCTA allow of a noninvasive quantification of the structural and vascular changes in OD and the macular zone and accurately distinguish between healthy eyes and eyes with POAG, showing an association with the presence and progression of glaucoma.
Keywords: angiography; disease progression; glaucoma, open-angle; macula lutea; optic disc; tomography, optical coherence